Construction of Papaya Male and Female BAC Libraries and Application in Physical Mapping of the Sex Chromosomes. (5th July 2011) - Gschwend, Andrea R.; Yu, Qingyi; Moore, Paul; Saski, Christopher; Chen, Cuixia; Wang, Jianping; Na, Jong-Kuk; Ming, Ray
Abstract : Papaya is a major fruit crop in the tropics and has recently evolved sex chromosomes. Towards sequencing the papaya sex chromosomes, two bacterial artificial chromosome (BAC) libraries were constructed from papaya male and female genomic DNA. The female BAC library was constructed using restriction enzyme Bst Y I and consists of 36, 864 clones with an average insert size of 104 kb, providing 10.3x genome equivalents. The male BAC library was constructed using restriction enzyme Eco R I and consists of 55, 296 clones with an average insert size of 101 kb, providing 15.0x genome equivalents. The male BAC library was used in constructing the physical map of the male-specific region of the male Y chromosome (MSY) and in filling gaps and extending the physical map of the hermaphrodite-specific region of the Y h chromosome (HSY) and the X chromosome physical map. The female BAC library was used to extend the X physical map gap. The MSY, HSY, and X physical maps offer a unique opportunity to study chromosomal rearrangements, Y chromosome degeneration, and dosage compensation of the papaya nascent sex chromosomes.